Future directions in the management of epithelial ovarian cancer. (June 2008) - Blagden, Sarah; Gabra, Hani
Epithelial ovarian cancer can be a difficult malignancy to manage, partially owing to its heterogenous biology. Whilst desirable, screening designed to reduce mortality has not yet proven effective, though results of ongoing studies are awaited. In this brief review, we attempt to highlight some important issues in the current management of primary and recurrent ovarian cancer, and to place these issues in the context of cutting-edge approaches to targeted therapy and its combination with chemotherapy, as well as other novel treatment strategies. It is hoped that this will lead to further improvements in progression-free and overall survival for patients with ovarian cancer, whilst maintaining their quality of life for as much of the disease journey as possible.